Acute ischemic stroke in tuberculous meningitis - Guo, Yi-Jia; Gan, Xin-Ling; Zhang, Ru-Yun; Liu, Yong; Wang, Er-Li; Lu, Shui-Hua; Jiang, Hui; Duan, Hong-Fei; Yuan, Zheng-Zhou; Li, Wei-Min (Frontiers in Public Health, 2024)
The underlying mechanism for stroke in patients with tuberculous meningitis (TBM) remains unclear. This study aimed to investigate predictors of acute ischemic stroke (AIS) in TBM, and whether AIS mediates the relationship between inflammation makers and functional disability.Methods: Between January 2011 and December 2021, TBM patients admitted into five hospitals were consecutively observed. Generalized linear mixed model and subgroup analyses were performed to investigate predictors with AIS in patients with and without vascular risk factors (VAF). Mediation analyses were performed to explore the potential causal chain in which AIS may mediate the relationship between neuroimaging makers of inflammation and 90-day functional outcome.: A total of 1353 patients with TBM were included. The percentage rate of AIS within 30 days after admission was 20.4 (95% CI 18.2-22.6). Multivariate analysis suggested that age≥35 (OR=1.49; 95% CI, 1.06-2.09; P=0.019), hypertension (OR=3.56; 95% CI, 2.42-5.24; P<0.001), diabetes (OR=1.78; 95% CI, 1.11-2.86; P=0.016), smoking (OR=2.88; 95% CI, 1.68-4.95; P<0.001), definite TBM (OR=0.19; 95% CI, 0.06-0.42; P<0.001), disease severity (OR=2.11; 95% CI, 1.50-2.90; P =0.056), meningeal enhancement (OR=1.66; 95% CI, 1.19-2.31; P=0.002), hydrocephalus (OR=2.98; 95% CI, 1.98-4.49; P<0.001) were associated with AIS. Subgroup indicated that disease severity (P for interaction=0.003), 5tuberculoma (P for interaction=0.008), and meningeal enhancement (P for interaction <0.001) were significant differences in patients with and without VAF. Mediation analyses revealed that the relationship between neuroimaging makers of inflammation and functional disability mediated by AIS was 16.98% (95% CI, 7.82%-35.12%) for meningeal enhancement, and 3.39% (95% CI 1.22%-6.91%) for hydrocephalus.Neuroimaging makers of inflammation were predictors of AIS in TBM patients. AIS mediates less than 20% of the association between inflammation and functional outcome at 90 days. More attention should be paid to clinical therapies targeting inflammation and hydrocephalus to improve functional outcomes directly.Key word Tuberculous meningitis, acute ischemic stroke, functional outcome.